Molecular dynamics of coalescence and collisions of silver nanoparticles - Guevara Chapa, Enrique; Mejía Rosales, Sergio (Springer Netherlands & Kluwer Academic Publishers, 2014)
We study how different relative orientations and impact velocity on the collision of two silver nanoparticles affect the first stages of the formation of a new, larger nanoparticle. In order to do this, we implemented a set of molecular dynamics simulations on the NVE ensemble on pairs of silver icosahedral nanoparticles at several relative orientations, that allowed us to follow the dynamics of the first nanoseconds of the coalescence processes. Using bond angle analysis, we found that the initial relative orientation of the twin planes has a critical role on the final stability of the resulting particle, and on the details of the dynamics itself. When the original particles have their closest twins aligned to each other, the formed nanoparticle will likely stabilize its structure onto a particle with a defined center and a low surface-to-volume ratio, while nanoparticles with misaligned twins will promote the formation of highly defective particles with a high inner energy.